5
$\begingroup$

Consider the following functional equation: $$f(x+y+z)=f(x)g(y)+f(y)g(z)+f(z)g(x)$$ where the equation holds for all $x,y,z \in \mathbb{R}$. One solution is $f(x)=cx$ and $g(x)=1$. What are all the continuous solutions $f, g\colon \mathbb{R} \to \mathbb{R}$?

(This was inspired by the question About the addition formula $f(x+y) = f(x)g(y)+f(y)g(x)$)

$\endgroup$
6
$\begingroup$

The problem has a simpler solution than I had originally anticipated. I don't want to be deleting too much stuff, so instead let me present the simple argument, and leave the rest as it was.

Lemma: Suppose that $f$ satisfies the relation $$ f(x+y+z) = \alpha( f(x)f(y)+f(y)f(z)+f(z)f(x) )+ \beta(f(x) + f(y) + f(z)).$$ where $\alpha,\beta$ are constants, $\alpha \neq 0$. Then $f$ is constant.

Proof: If $f$ is constant, we are done, so suppose that this is not the case. Rewrite the relation as: $$ f(x+y+z) = f(x) ( \alpha f(y)+ \alpha f(z)+ \beta)+ \alpha f(y)f(z) + \beta( f(y) + f(z)).$$ Let $y = w +t$, $z = w-t$, and define $k(w,t) := \alpha f(y)+ \alpha f(z)+ \beta$ and $l(w,t) = \alpha f(y)f(z) + \beta( f(y) + f(z))$. Then the above relation says: $$ f(x+2w) = f(x)k(w,t) + l(w,t).$$ Thus, for any $\xi \in f(\mathbb R)$, and any $t_0$ we have: $$ \xi k(w,t) + l(w,t) = f(x+2w) = \xi k(w,t_0) + l(w,t_0).$$ Because $\xi $ can take at least two different values, we have $ k(w,t) = k(w,t_0)$ and $l(w,t) = l(w,t_0)$. Thus, $k(w,t)$ and $l(w,t)$ really depend only on $w$. Looking at $k$, we conclude that: $$ f(w+t) + f(w-t) = 2f(w),$$ and hence we may write $f(w+t) =f(w) + r_w(t)$ where $r_w$ is a continuous function with $r_w(-t) = -r_w(t)$. Next, looking at $l(w,x)$ we find that: $$(f(w) - r_w(t))(f(w) + r_w(t)) = f(w)^2$$ But after reducing the left side, this leads to $r_w(t)^2 = 0$, and hence $r_w(t) = 0$. Since $r,w$ were arbitrary, we conclude that $f$ is constant, which finishes the proof.

Having this, we can simplify the following argument a lot, and dispose of the additional assumption that $f$ is differentiable.

Original post:

Lemma: We can assume that $g$ is of the form $g(x) = \alpha f(x) + \beta$ for some constants $\alpha, \beta$.

Proof: Plug in $z = y = 0$. Then we get: $$ f(x) = f(x) g(0) + f(0)(g(0) + g(x)).$$ If $f(0) \neq 0$, we can solve the above for $g(x)$ and get the answer of the desired form. So, suppose for a moment that $f(0) = 0$, and consequently also $g(0) = 1$ or $f$ is constantly $0$. Then, we plug in $z = 0$ to the functional equation. This leads to: $$ f(x+y) = f(x)g(y) + f(y) = f(y) g(x) + f(x).$$ Hence we have: $$ f(x)( g(y) - 1) = f(y)(g(x) - 1) $$ If $y$ is any value with $f(y) \neq 0$ we find $g(x)$ of the sought form.

Thus, we have reduced the problem to solving the equation: $$ f(x+y+z) = \alpha( f(x)f(y)+f(y)f(z)+f(z)f(x) )+ \beta(f(x) + f(y) + f(z)).$$ where $\alpha,\beta$ are constants. The case $\alpha = 0$ reduces to Cauchy linear equation. Then, $f$ is affine: $f(x) = ax +b$ for some $a,b$; so suppose this is not the case.

To make things slightly simpler, suppose that $f$ is also differentiable. Then, differentiating with respect to $x$ we get: $$ f'(x+y+z) = \alpha f'(x) (f(y) + f(z) + \gamma) $$ where $\gamma = \beta/\alpha$. Let $\gamma_z = \gamma + f(z)$. Using the symmetry in the above equality, we get: $$\alpha f'(x) (f(y) +\gamma_z) = \alpha f'(y) (f(x) +\gamma_z) $$ which reduces to $$ \frac{f'(x)}{f(x) +\gamma_z} = \frac{f'(y)}{f(y) +\gamma_z}$$ whenever the division is possible. If we fix $z$ and $x_0$ such that $f(x_0) + \gamma_z \neq 0$, then in a neighbourhood of $x_0$, the function $h(x) := \frac{f'(x)}{f(x) +\gamma_z} $ is well defined and constant: $h(x) = c_z$, as long as this neighbourhood (together with the boundary) has no points $x$ with $f(x) = -\gamma_z$. (This can be done, unless $f$ is constant, but that case is trivial.)

Letting $f_z(x) := f(x) +\gamma_z$ we find that: $f_z'(x) = c_z f_z(x) $, and consequently $f(x) = A_z e^{c_z x} - \gamma_z$ for some constant $A_z$ ( $A_z, c_z $ may depend on $x_0$ implicitly). But then $f(x)$ is bounded away from $-\gamma_z$ on the neighbourhood we are considering. Hence, we can always extend the neighbourhood, and consequently we nay assume that $f(x) = A_z e^{c_z x} - \gamma_z$ for all real $x$. Fix some choice of $z$; letting $A=A_z,c=c_z,d = \gamma_z$ we get $$f(x) = A e^{cx} + d$$.

Now, we are in trouble. If we plug in the form for $f$ obtained above to the functional equation we started with, and take $x=y=z$ we get: $$ Ae^{3x} + d = 3 \alpha A e^{2x} + 3 \beta e^x + ...$$ which is a contradiction, because the two sides have a different order of growth.

Thus, it follows that it remains to check the case when $f$ is affine, and $g$ is affine as well. This should is simple enough. Indeed, suppose that $f(x) = ax + b$, $g(x) = cx + d$. If $f$ is constantly $0$, then any $g$ will do, so suppose that it's not the case. If $f$ is constant, but non-zero, then $g(x) =1/3$ for all $x$. Suppose now that $a \neq 0$. Then we get from the functional equation: $$ x+y+z + \dots = ac( xy + yz + zx) + \dots,$$ which is only possible when $c = 0$, so $g$ is constant, $g(x) = d$. But now we get: $$ a(x+y+z) + b = d( ax + ay + az + 3b).$$ Comparing the leading terms, we find that $d = 1$, and hence $b = 0$. Thus, $f(x) = ax,\ g(x) = 1/3$.

To sum up, the solutions are $f(x) = ax,\ g(x) = 1$; $f(x) = b,\ g(x) = 1/3$; $f(x) = 0,\ g(x) = ...$.

$\endgroup$
  • $\begingroup$ @Malper: Sorry, there was a typo in the definition; now corrected. $\endgroup$ – Jakub Konieczny Jan 15 '14 at 15:54
2
$\begingroup$

If $f$ is constant then $g(x)=\frac{1}{3}$. Another noted solution is $f(x)=cx$ and $g(x)=1.$ Assuming $f$ and $g$ are thrice differentiable, these are the only solutions.

(Spoiler alert.) The proof just uses differentiation of the functional equation.
\begin{eqnarray*} f(x+y+z)-f(x)g(y)-f(y)g(z)-f(z)g(x)&=&0\\ f'(x+y+z)-f'(x)g(y)-f(z)g'(x)&=&0\\ f''(x+y+z)-f'(z)g'(x)&=&0\\ f'''(x+y+z)&=&0\\ f''(\cdot)&=&c_1\\ f'(z)&=&c_1z+c_2\\ c_1&=&(c_1z+c_2)g'(x)\\ 0&=&c_1g'(x)\\ \end{eqnarray*} Suppose $g$ is not constant. Then \begin{eqnarray*} c_1&=&0\\ f''(\cdot)&=&0\\ f(x)&=&c_2x+c_3\\ c_2&=&c_2g(y)+(c_2z+c_3)g'(x)\\ 0&=&c_2g'(y)\\ c_2&=&0\\ f(x)&=&c_3 \end{eqnarray*} So $f$ is constant. But then $g$ is constant. Therefore, in any case $g$ must be constant. Suppose $f$ is not constant. Then \begin{eqnarray*} g'(x)&=&0\\ c_1&=&0\\ f''(\cdot)&=&0\\ f(x)&=&c_2x+c_3\\ c_2&=&c_2g(y)+(c_2z+c_3)g'(x)\\ g(\cdot)&=&1\\ f(0+0+0)&=&3f(0)\\ f(0)&=&0\\ f(x)=c_2x\\ \end{eqnarray*}

This holds wherever $f$ and $g$ are thrice differentiable. It might be interesting to construct a solution from nowhere differentiable functions.

$\endgroup$
  • $\begingroup$ what derivative the prime is among the three $\frac{\partial}{\partial x}, \frac{\partial}{\partial y},\frac{\partial}{\partial z}$?? $\endgroup$ – janmarqz Jan 14 '14 at 23:46
  • $\begingroup$ The functions $f$ and $g$ are univariate, so $f'$ has just one meaning. In the chain of equations above, I differentiate with respect to different variables, the first three being $x$, $z$ and $y$. $\endgroup$ – Steve Mitchell Jan 15 '14 at 1:15
  • $\begingroup$ $x+y+z$ depends on three variables $\endgroup$ – janmarqz Jan 15 '14 at 1:21
  • $\begingroup$ Suppose $h(x,y,z)=f(x+y+z)$. Then $\frac{\partial h}{\partial x}=f'(x+y+z)\frac{\partial x}{\partial x}$. $\endgroup$ – Steve Mitchell Jan 15 '14 at 1:41
  • $\begingroup$ ok, prime for that partial $\endgroup$ – janmarqz Jan 15 '14 at 1:43
1
$\begingroup$

Here's a proof equivalent to @Feanor's but expressed a little differently. Even continuity does not seem to be a required assumption.

The solution is understood if $f$ or $g$ are constant, so assume neither is constant, and draw a contradiction.

From $x=y=z=0$, we conclude $f(0)=3f(0)g(0)$, so we have either $f(0)=0$ or $g(0)=\frac{1}{3}$.

Case I: $f(0)=0$

From $y=z=0$ we have $f(x)=f(x)g(0)$, so $g(0)=1$.

From $y=-x,\;z=0$ we have $0=f(0)=f(x)g(-x)+f(-x)$, or $f(x)g(-x)=-f(-x)$.

From $z=-y$ we have \begin{eqnarray*} f(x)&=&f(x)g(y)+f(y)g(-y)+f(-y)g(x)\\ f(x)[1-g(y)]&=&f(-y)[g(x)-1]\\ \frac{f(x)}{g(x)-1}&=&\frac{-f(-y)}{g(y)-1}=d \end{eqnarray*} The constant $d\neq 0$; let $b=1/d$. From this we conclude $g(x)=bf(x)+1$ and $f(x)+f(-x)=0$. (These hold even when $g(x)=1$.)

Finally, from $y=0,\;z=-x$ we have \begin{eqnarray*} 0=f(0)&=&f(x)g(y)+f(y)g(z)+f(z)g(x)\\ &=&f(x)[1-g(x)]\\ &=&-bf(x)^2 \end{eqnarray*} This is our contradiction, since $f$ is not constant.

Case II: $g(0)=\frac{1}{3}$

This is similar to Case I, so I'll spare the algebra. The cases are mutually exclusive: if $f(0)=0$, then we have seen that $g(0)=1$. Denote $c=f(0)\neq 0$.

From $y=z=0$ we have $g(x)=\frac{2}{3c}f(x)-\frac{1}{3}$.

From $z=-y$ we can derive $f(y)+f(-y)=2c$.

Finally, from $y=0,\;z=-x$ we derive $0=(f(x)-c)^2$, our contradiction.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.